PSYCHOLOGICAL AND DIDACTIC FEATURES OF GROUP WORK OF PRIMARY SCHOOL STUDENTS - L.M. Shevchuk (Academy of Cognitive and Natural Sciences, 2010)
The article is dedicated to the psychological-didactic peculiarities of pupils' group work at primary school, in particular to the specificity of its using on the basis of taking into account younger schoolchildren's age and individual peculiarities.